2013
DOI: 10.1136/annrheumdis-2012-202781
|View full text |Cite
|
Sign up to set email alerts
|

Association between testosterone levels and risk of future rheumatoid arthritis in men: a population-based case–control study

Abstract: Lower levels of testosterone were predictive of RF-negative RA, suggesting that hormonal changes precede the onset of RA and affect the disease phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…In their study of 32 males in Finland, Heikkila et al [11] reported no association between baseline serum testosterone levels and the subsequent development of rheumatoid arthritis. By contrast, in their nested case–control study of 278 patients, Pikwer et al [12] reported that low serum testosterone was predictive of RF-negative rheumatoid arthritis. A small number of clinical trials have also yielded conflicting results.…”
Section: Discussionmentioning
confidence: 95%
“…In their study of 32 males in Finland, Heikkila et al [11] reported no association between baseline serum testosterone levels and the subsequent development of rheumatoid arthritis. By contrast, in their nested case–control study of 278 patients, Pikwer et al [12] reported that low serum testosterone was predictive of RF-negative rheumatoid arthritis. A small number of clinical trials have also yielded conflicting results.…”
Section: Discussionmentioning
confidence: 95%
“…But the exact role of sex hormones in the pathogenesis and progression of lung cancer remains unclear, and there are actually some dramatic discrepancies in publishing reports. For example, certain studies suggested that androgens such as testosterone were decreased whereas estrogens such as estradiol were increased in patients with lung cancer (12,18). But in other studies, there were no such associations observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, low levels of testosterone have been associated with an increased risk of autoimmune rheumatoid arthritis (RA) in men (79) and, in addition, testosterone can suppress superoxide production and microbicidal activity in neutrophils, and thus influence the inflammatory response (80). Furthermore, an increase in testosterone levels suppresses the expression of the pro-inflammatory cytokines, such as TNFα, IL-1β, and IL-6 and potentiate the expression of the anti-inflammatory cytokine IL-10 (81, 82), which has been shown to inhibit neutrophil phagocytic and bactericidal activity, and down-regulate some cell-surface proteins, such as CD11b, pointing toward a less mature phenotype (83, 84).…”
Section: Discussionmentioning
confidence: 99%